Improving, Restoring, and Managing Natural Resources in Florida: Sources of Technical Assistance for Urban Homeowners - Mark Hostetler; Martin Main; Chris Demers (EDIS)
The purpose of this document is to summarize sources of information from federal, state, and non-governmental organizations that provide technical assistance to urban landowners interested in conserving natural resources (Table 1). This document is WEC-193, one of a series of the Wildlife Ecology and Conservation Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date November 2004.